Механические и теплофизические свойства композита АlN – SiC - Фесенко, И.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
Pressureless sintered AlN based composites contain uniformly distributed particles of SiC. The ceramic composite samples are characterized by Vicker’s hardness of 13.2–15.6 GPa (load of 15 kg), fracture toughness of 3.8–4.3 MPa∙m⁰∙⁵ and thermal conductivity of 47–55 W/(m∙К). Testing of AlN–SiC composite showed the possibility of its use as a cutting tool material.